Efektivitas Media Edpuzzle Dalam Meningkatkan Maharah Istimā' Mahasiswa - Arif Widodo (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examined the effectiveness of Edpuzzle in improving university students’ Arabic listening skills (maharah istimā’). A quantitative pre-experimental one-group pretest-posttest design was employed. The participants were 20 second-semester students of the Arabic Language Education Program at Universitas Sunan Drajat Lamongan. Data were collected using listening tests, a student-response questionnaire, and an observation sheet. Test data were analyzed using descriptive statistics, the Shapiro-Wilk test, the Wilcoxon signed-rank test, rank-biserial correlation, and normalized gain. The mean score increased from 80.50 in the pretest to 84.00 in the posttest, while the median increased from 85.00 to 92.00. Nineteen students improved and one student declined. Because the score differences were not normally distributed (W = 0.297, p < .001), the Wilcoxon test was used and indicated a significant difference between pretest and posttest scores (W = 20.00, p = .001), with a large rank-biserial effect size of .810. The mean normalized gain was .296 (low), whereas the median was .467 (moderate), a discrepancy driven by one extreme posttest decline. Across 14 analyzable questionnaire items, the average positive response was 93.3%. Classroom observation yielded 40 out of 40 points (100%), categorized as very good. Edpuzzle was therefore associated with improved Arabic listening performance and positive learning responses. Nevertheless, causal interpretation is limited by the absence of a control group, the small sample, and one score pair requiring verification.